Kubord 1 - Word frequencies Sydsvenskan 2020 - Språkbanken Text (University of Gothenburg, 2024)
Part of the collection Kubord 1

Del av samlingen Kubord 1
Kubord 1 - Ordfrekvenser Sydsvenskan 2020
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik